A critical review of traditional and emerging techniques and fluids for electronics cooling. (October 2017) - Sohel Murshed, S.M.; Nieto de Castro, C.A.
Abstract: Continued miniaturization and demand for high-end performance of electronic devices and appliances have led to dramatic increase in their heat flux generation. Consequently, conventional coolants and cooling approaches are increasingly falling short in meeting the ever-increasing cooling needs and challenges of those high heat generating electronic devices. This study provides a critical review of traditional and emerging cooling methods as well as coolants for electronics. In addition to summarizing traditional coolants, heat transfer properties and performances of potential new coolants such as nanofluids are also reviewed and analyzed. With superior thermal properties and numerous benefits nanofluids show great promises in fulfilling the cooling demands of high heat generating electronic devices. It is believed that applications of such novel coolants in emerging techniques like micro-channels and micro-heat pipes can revolutionize cooling technologies for electronics in the future.